PEMODELAN EPS DAN ROE MENGGUNAKAN METODE REGRESI MULTIVARIAT MELALUI UJI MANOVA - Mulawarman Awaloedin; Jasmine Avrilia Fahada; Anneke Sayarifah Qatrunnada (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze the simultaneous influence of financial and operational ratios on two main indicators of company performance, namely Earnings per Share (EPS) and Return on Equity (ROE), in the tourism and hospitality sectors. Using the multivariate regression approach and the MANOVA test, this study examines the financial data of a star hotel that listed its shares on the Indonesian stock exchange for the period 2010–2024. The variables analyzed included Occupancy Rate, ADR, Current Ratio, Gross Operating Profit (GOP), Net Operating Profit (NOP), Debt to Equity Ratio (DER), and Debt to Asset Ratio (DAR). The regression model was shown to meet all classical assumptions and had high predictive power (R² > 97%). The results of the MANOVA test showed that only Net Operating Profit (NOP) had a significant effect on EPS and ROE simultaneously (Wilks' Lambda = 0.0014; p = 0.0001). These findings confirm that operational profitability is a key determinant of shareholder value, especially in the context of post-crisis recovery. This research makes a strategic contribution to financial decision-making in tourism companies operating in a volatile economic environment. Keywords: Earnings per Share (EPS), Return on Equity (ROE), Net Operating Profit (NOP), Financial Performance, Tourism Industry